Two-dimensional transition metal sulfide nanosheet and preparation method thereof

By using discharge-treated sulfide polyacrylonitrile as a sulfur source, the defect density of two-dimensional transition metal sulfide nanosheets is reduced, the problem of high defect density in the prior art is solved, the preparation of high-quality materials is realized, and its application potential is expanded.

CN119615106AActive Publication Date: 2025-03-14TSINGHUA SHENZHEN INTERNATIONAL GRADUATE SCHOOL
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411577369.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-03-14
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

In the prior art, the defect density of two-dimensional transition metal sulfide nanosheets is high, resulting in a degradation of electrical performance and it is difficult to meet the application needs of high-performance electronic devices.

Method used

Using discharge-treated sulfide polyacrylonitrile as the sulfur source, two-dimensional transition metal sulfide nanosheets are grown under specific conditions by chemical vapor deposition, providing highly active single-atom sulfur to reduce defect density.

Benefits of technology

It significantly reduces the defect density of two-dimensional transition metal sulfide nanosheets, improves its crystal quality and optical properties, and broadens its application prospects in the fields of optics, electricity, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615106A_ABST
    Figure CN119615106A_ABST
Patent Text Reader

Abstract

The invention discloses a two-dimensional transition metal sulfide nanosheet and a preparation method thereof. According to the two-dimensional transition metal sulfide and the preparation method thereof, a sulfur source and a transition metal source are used as preparation raw materials to perform chemical vapor deposition reaction on a substrate to grow the two-dimensional transition metal sulfide; the sulfur source is sulfurized polyacrylonitrile subjected to discharge treatment, the transition metal source is one of molybdenum trioxide, tungsten trioxide or manganese dioxide, and the carrier gas is argon or nitrogen. According to the preparation method provided by the invention, the two-dimensional transition metal sulfide nanosheet with low defect density, high crystal quality and excellent optical performance can be obtained, and the preparation method has a wide application prospect in the fields of high-performance electronic devices and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of two-dimensional semiconductor material preparation, and specifically relates to a two-dimensional transition metal sulfide nanosheet and a preparation method thereof. Background Art

[0002] Over the past half century, semiconductor materials represented by silicon have greatly promoted the development of electronic information technology. In this context, the size of electronic devices has been continuously miniaturized. However, when the thickness of traditional semiconductors (such as silicon, germanium, and III-V compounds) is reduced to nanometer size, the surface dangling bonds and surface electronic state effects will significantly reduce their electrical performance, and the uniformity and reliability of the devices will be reduced, making it difficult to meet application requirements. Therefore, finding and developing new semiconductor materials is an inevitable trend in the development of information technology, and it is also a frontier direction of condensed matter physics, materials science, information science, and technology.

[0003] In recent years, two-dimensional semiconductor materials represented by two-dimensional transition metal sulfides have been regarded as one of the ideal candidate materials for continuing Moore's Law in the post-silicon semiconductor era due to their characteristics of no surface dangling bonds, high mobility, ultra-large specific surface area, flexibility, and easy planar integration. The latest International Device and Semiconductor Roadmap Committee pointed out that two-dimensional semiconductor materials with atomic-level thickness not only have efficient carrier transport capabilities on a two-dimensional plane under quantum confinement and a variety of excellent physical properties, but are also compatible with classical complementary metal oxide semiconductor (CMOS) technology, and are expected to extend Moore's Law to below the 2nm node. However, the two-dimensional transition metal sulfide crystals reported so far are of low quality and have a large number of point defects. These defects are scattering centers for carriers, which will greatly reduce the mobility of the device, thereby causing a significant decrease in electrical performance. Therefore, the development of efficient preparation technology for high-quality, low-point defect density two-dimensional transition metal sulfides is a prerequisite for realizing their application.

[0004] As one of the most commonly used methods in industry and laboratories, chemical vapor deposition can directly deposit the products of gas-phase reactions on a specified substrate or generate materials on the substrate surface to obtain atomic-level flakes or films, which is conducive to the preparation of large-area, high-quality two-dimensional transition metal sulfide nanosheets. However, the defect density of two-dimensional transition metal sulfide nanosheets prepared by traditional chemical vapor deposition is still much higher than that of traditional semiconductor materials. To solve the above problems, researchers have improved the quality of molybdenum disulfide nanosheets by controlling and optimizing the reactants, substrates, reaction temperature and reaction time in chemical vapor deposition. For example, researchers have used recondensed sulfur blocks as a sulfur source to provide a stable sulfur source supply for the reaction system, achieving large-area uniformly distributed two-dimensional transition metal sulfide nanosheets, but there are still many defects in the samples; some researchers have also used sulfur vapor to pre-sulfurize the substrate to directly grow two-dimensional transition metal sulfide nanosheets with lower defect density, but these methods have very limited effects on reducing the defect density of two-dimensional transition metal sulfide nanosheets, and the defect density of the resulting materials is still high, and the quality of the materials needs to be further improved. In summary, how to further reduce the defect density of the prepared two-dimensional transition metal sulfide nanosheets is a major challenge facing this field. Researchers need to further improve and optimize the preparation method, improve the controllability and universality of the preparation method, and then reduce the defect density of such materials and improve their crystal quality, thereby promoting their application in high-performance electronic devices. Summary of the invention

[0005] The present invention aims to solve at least one of the above technical problems existing in the prior art. To this end, the present invention provides a two-dimensional transition metal sulfide nanosheet having good morphology, optical properties and crystal quality, and having broad application prospects in the fields of optics, electricity, etc.

[0006] The invention also provides a method for preparing two-dimensional transition metal sulfide nanosheets.

[0007] The first aspect of the present invention provides a method for preparing two-dimensional transition metal sulfide nanosheets, which comprises sulfide polyacrylonitrile powder subjected to discharge treatment, wherein the metal source is at least one of molybdenum trioxide powder, tungsten trioxide powder or manganese dioxide powder.

[0008] A technical solution in the method for preparing two-dimensional transition metal sulfide nanosheets of the present invention has at least the following beneficial effects:

[0009] Due to the easy availability of sublimated sulfur powder, sulfur powder is often used as a sulfur source in the current chemical vapor deposition method to prepare two-dimensional transition metal sulfide nanosheets. However, the present invention has found that sulfur powder will produce sulfur species mainly composed of long-chain sulfur after heating and volatilization. The reaction activity of these long-chain sulfurs is low, and it is difficult to inhibit or heal the large number of sulfur defects generated during the growth process, resulting in many crystal defects and low quality. The highly active single-atom sulfur has the most negative adsorption energy with sulfur vacancies, that is, it is most easily adsorbed on sulfur vacancies and then heals and inhibits sulfur vacancy defects during the growth process, thereby further reducing the defect density of the material. The present invention further found that the sulfurized polyacrylonitrile obtained from the discharged lithium-sulfur battery can efficiently and selectively release single-atom sulfur and does not contain any other form of sulfur. Therefore, the obtained sulfurized polyacrylonitrile can be used as a new sulfur source for chemical vapor deposition, providing highly active single sulfur as a sulfur source during the growth process, thereby preparing two-dimensional transition metal sulfide nanosheets with ultra-low density defects.

[0010] The present invention uses sulfide polyacrylonitrile treated by discharge as a sulfur source, and the activity of the sulfur source is higher (the released single atomic sulfur plays a role), which improves the problem of low activity of traditional sulfur sources, so the quality of the prepared molybdenum disulfide nanosheets is higher and the defect density is lower. The activity of the sulfur source is higher, on the one hand, it means that through theoretical calculation, it is found that the activity of single atomic sulfur is higher, and it has the most negative adsorption energy with the sulfur vacancy in molybdenum disulfide, so it can effectively repair and inhibit the defects generated during the growth process; on the other hand, because the chemical structure of sulfide polyacrylonitrile is changed by discharge treatment (lithium atoms are introduced into the structure), the energy of releasing single atomic sulfur is greatly reduced, and single atomic sulfur can be selectively released at a specific temperature without producing other low-activity sulfur species, which enhances its effectiveness as a sulfur source. The energy of releasing single atomic sulfur from other sulfur sources such as sulfur powder and undischarged sulfide polyacrylonitrile is much higher than that of discharged sulfide polyacrylonitrile, and single atomic sulfur cannot be selectively released for the growth process.

[0011] According to some embodiments of the present invention, in the chemical vapor deposition reaction, the heating temperature of the sulfur source is 100-500°C.

[0012] According to some embodiments of the present invention, in the chemical vapor deposition reaction, the heating temperature of the sulfur source is 150-450°C.

[0013] According to some embodiments of the present invention, in the chemical vapor deposition reaction, the heating temperature of the sulfur source is 380-420°C.

[0014] In some embodiments of the present invention, in the chemical vapor deposition reaction, the heating rate of the sulfur source is 15 to 55° C. / min.

[0015] In some embodiments of the present invention, in the chemical vapor deposition reaction, the heating rate of the sulfur source is 35-45° C. / min.

[0016] According to some embodiments of the present invention, in the chemical vapor deposition reaction, the heating temperature of the transition metal source is 400-1200°C.

[0017] In some embodiments of the present invention, in the chemical vapor deposition reaction, the temperature of the transition metal source is 550-1100°C.

[0018] In some embodiments of the present invention, in the chemical vapor deposition reaction, the temperature of the transition metal source is 680-850°C.

[0019] In some preferred embodiments of the present invention, when the transition metal source is molybdenum trioxide, the temperature of the transition metal source is 650-820° C. during the chemical vapor deposition reaction.

[0020] In some preferred embodiments of the present invention, when the transition metal source is tungsten trioxide, the temperature of the transition metal source is 700-850° C. during the chemical vapor deposition reaction.

[0021] In some preferred embodiments of the present invention, when the transition metal source is manganese dioxide, the temperature of the transition metal source is 550-800° C. during the chemical vapor deposition reaction.

[0022] In some embodiments of the present invention, in the chemical vapor deposition reaction, the heating rate of the transition metal source is 15 to 50° C. / min.

[0023] In some embodiments of the present invention, in the chemical vapor deposition reaction, the heating rate of the transition metal source is 25-45° C. / min.

[0024] The temperature of the transition metal source is positively correlated with the size of the two-dimensional transition metal sulfide nanosheets.

[0025] According to some embodiments of the present invention, the chemical vapor deposition reaction is performed with the assistance of a carrier gas.

[0026] According to some embodiments of the present invention, the carrier gas comprises at least one of nitrogen and argon.

[0027] According to some embodiments of the present invention, relative to the flow direction of the carrier gas, the sulfur source is located upstream of the metal source, and the substrate is located above the metal source.

[0028] Such a position setting is more conducive to balancing the deposition rates of the sulfur source and the transition metal source on the substrate. At the same time, the growth of the two-dimensional transition metal sulfide nanosheets and the volatilization of the transition metal source require a high temperature zone, while the volatilization of the sulfur source requires a low temperature zone, so the sulfur source is placed upstream.

[0029] In some embodiments of the present invention, the vertical distance between the transition metal source and the substrate is 0.3-3 mm.

[0030] In some preferred embodiments of the present invention, the vertical distance between the transition metal source and the substrate is about 1.2 mm.

[0031] In some embodiments of the present invention, the insulation time of the chemical vapor deposition reaction is 0 to 50 minutes.

[0032] In some embodiments of the present invention, the insulation time of the chemical vapor deposition reaction is 2 to 25 minutes.

[0033] The insulation time has a certain positive correlation with the size of the molybdenum disulfide nanosheets.

[0034] In some embodiments of the present invention, the pressure of the chemical vapor deposition reaction is 0.05 to 760 torr.

[0035] The pressure of the chemical vapor deposition reaction is the pressure in the environment where the sulfur source and the molybdenum source are located; for example, when the instrument for the chemical vapor deposition reaction is a tubular furnace, the pressure is the pressure in the quartz tube of the tubular furnace.

[0036] In some embodiments of the present invention, the chemical vapor deposition reaction is performed with the assistance of a carrier gas.

[0037] In some embodiments of the present invention, the flow rate of the carrier gas is 50 to 180 sccm.

[0038] In some embodiments of the present invention, the chemical vapor deposition reaction process comprises the following steps:

[0039] S1. placing the sulfur source and the transition metal source in a heating zone;

[0040] S2. A carrier gas is introduced for gas replacement, wherein the direction of the carrier gas introduction should satisfy the flow from the sulfur source to the molybdenum source;

[0041] S3. During the carrier gas flow, heating the sulfur source and the transition metal source and keeping them warm;

[0042] S4. Cooling down the system obtained in step S3.

[0043] In some embodiments of the present invention, in step S3, the heating should satisfy that the time when the sulfur source reaches the preset temperature is earlier than or equal to the time when the transition metal source reaches the preset temperature, so that the chemical vapor deposition reaction has a sulfur-rich environment.

[0044] In some embodiments of the present invention, in step S4, the cooling rate of the cooling has no significant effect on the result of the chemical vapor deposition reaction, and those skilled in the art may perform at least one of natural cooling and human intervention cooling according to actual needs.

[0045] In some embodiments of the present invention, the molar ratio of the transition metal source to the sulfur source is 1:3-200.

[0046] It is understood that the molar ratio of the transition metal source to the sulfur source may be any one of 1:10, 1:50, 1:100, 1:150 and 1:200 or a range formed by any two of them, such as 1:10-100.

[0047] According to some embodiments of the present invention, the substrate comprises silicon dioxide, sapphire or mica.

[0048] According to some embodiments of the present invention, the method for preparing the discharge-treated sulfurized polyacrylonitrile powder includes: assembling the sulfurized polyacrylonitrile as a positive electrode of a lithium-sulfur battery and subjecting the battery to a constant current discharge treatment.

[0049] According to some embodiments of the present invention, the current magnitude is 0.1C.

[0050] According to some embodiments of the invention, the discharge time is 10 hours.

[0051] According to some embodiments of the present invention, the method for preparing the discharge-treated sulfide polyacrylonitrile powder further includes collecting the discharge-treated sulfide polyacrylonitrile powder, washing it with N-methylpyrrolidone and anhydrous ethanol, and drying it in sequence, and the collected black powder is the discharge-treated sulfide polyacrylonitrile powder.

[0052] According to some embodiments of the present invention, a molar ratio of the metal source to the sulfur source is 1:3-150.

[0053] The second aspect of the present invention provides a two-dimensional transition metal sulfide nanosheet, which is prepared by the preparation method of the first aspect of the present invention.

[0054] According to some embodiments of the present invention, the point defect density of the two-dimensional transition metal sulfide nanosheet is ≤10 13 Pieces / cm 2 .

[0055] According to some embodiments of the present invention, the thickness of the two-dimensional transition metal sulfide nanosheet is 0.7-10 nm.

[0056] According to some embodiments of the present invention, the crystal domain size of the two-dimensional transition metal sulfide nanosheet is 5 to 100 μm.

[0057] One of the technical solutions of the present invention regarding two-dimensional transition metal sulfide nanosheets has at least the following beneficial effects:

[0058] Since the two-dimensional transition metal sulfide nanosheet provided by the present invention has the above parameters, it has good morphology, optical properties and crystal quality, and has broad application prospects in the fields of optics, electricity, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 This is a schematic diagram of the growth process of the two-dimensional transition metal sulfide nanosheets of the present invention.

[0060] Figure 2 This is a schematic diagram of the process of obtaining the sulfide polyacrylonitrile that has undergone discharge treatment in Example 1.

[0061] Figure 3 Schematic diagram of the relative positions of various components in the chemical vapor deposition method in Example 1.

[0062] Figure 4 This is an optical microscope image of the two-dimensional transition metal sulfide nanosheet of Example 1.

[0063] Figure 5 This is an atomic force microscope height image of the two-dimensional transition metal sulfide nanosheet of Example 1.

[0064] Figure 6 This is a fluorescence microscope image of the two-dimensional transition metal sulfide nanosheet of Example 1.

[0065] Figure 7 This is the Raman spectrum of the two-dimensional transition metal sulfide nanosheet of Example 1.

[0066] Figure 8 This is an optical microscope image of the two-dimensional transition metal sulfide nanosheet of Example 2.

[0067] Fig. 9 This is an atomic force microscope height image of the two-dimensional transition metal sulfide nanosheet of Example 2.

[0068] Fig.10 This is the Raman spectrum of the two-dimensional transition metal sulfide nanosheet of Example 2.

[0069] Fig.11This is an optical microscope image of the two-dimensional transition metal sulfide nanosheet of Example 3.

[0070] Fig.12 This is an atomic force microscope height image of the two-dimensional transition metal sulfide nanosheet of Example 3.

[0071] Fig.13 This is an optical microscope image of the molybdenum disulfide nanosheets obtained in Comparative Example 1.

[0072] Fig.14 This is an optical microscope image of the molybdenum disulfide nanosheets obtained in Comparative Example 2.

[0073] Fig.15 This is the room temperature photoluminescence spectrum of the two-dimensional transition metal sulfide nanosheet of Example 1.

[0074] Fig.16 This is the low-temperature photoluminescence spectrum of the two-dimensional transition metal sulfide nanosheet of Example 1.

[0075] Fig.17 This is the room temperature photoluminescence spectrum of the two-dimensional transition metal sulfide nanosheet of Example 2.

[0076] Fig.18 This is the room temperature photoluminescence spectrum of the molybdenum disulfide nanosheets obtained in Comparative Example 1.

[0077] Fig.19 This is the low-temperature photoluminescence spectrum of the molybdenum disulfide nanosheets obtained in Comparative Example 1.

[0078] Fig. 20 This is the room temperature photoluminescence spectrum of the two-dimensional transition metal sulfide nanosheet of Comparative Example 2.

[0079] Fig.21 This is a scanning transmission electron micrograph of the two-dimensional transition metal sulfide nanosheet of Example 1. DETAILED DESCRIPTION

[0080] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0081] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0082] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.

[0083] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.

[0084] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0085] Example 1

[0086] In this embodiment, a two-dimensional transition metal sulfide nanosheet is prepared. The process is as follows Figure 1 shown.

[0087] The specific preparation process is:

[0088] D1. Obtaining the sulphurized polyacrylonitrile after discharge treatment. Wherein:

[0089] In the first step, sulfur powder and polyacrylonitrile powder were mixed in a mass ratio of 4:1 by a grinding method; then the mixture was annealed at 330° C. for 450 min in an argon atmosphere to obtain the original vulcanized polypropylene.

[0090] In the second step, the original sulfide polyacrylonitrile is assembled as the positive electrode of the lithium-sulfur battery, and the battery is discharged at a constant current with a current of 0.1C and a discharge time of 10 hours. The sulfide polyacrylonitrile powder that has been discharged is collected and washed and dried with N-methylpyrrolidone and anhydrous ethanol solvent in turn. The black powder collected is the target sulfide polyacrylonitrile that has been discharged.

[0091] The process diagram of this step is as follows Figure 2 shown.

[0092] D2. Preparation for chemical vapor deposition: Take 300 mg of sulfide polyacrylonitrile treated with discharge and place it in a quartz boat, and place the quartz boat in the first heating zone of a one-inch (quartz tube diameter) tube furnace. Take 1.5 mg of molybdenum trioxide and mix it in another quartz boat, place the silicon dioxide substrate face down 1 mm above the quartz boat, and place the quartz boat in the second heating zone downstream of the first heating zone of the tube furnace; the upstream or downstream in the specific implementation method is based on the flow direction of the carrier gas; the specific placement position and the carrier gas flow direction are as follows: Figure 3 As shown; chemical vapor deposition is carried out in a tube furnace.

[0093] D3. Chemical vapor deposition: Argon gas was continuously introduced as a carrier gas at a flow rate of 80 sccm, wherein the flow direction of the argon gas was from the sulfur source to the molybdenum source, and the gas pressure in the quartz tube of the tube furnace was 1 atmosphere, i.e. 760 torr;

[0094] After ventilating the air in the tubular furnace for 10 minutes, heat the first heating zone (sulfur source) to 150°C and the second heating zone (molybdenum source) to 700°C at a rate of 35°C / min. The time to start heating the first heating zone and the second heating zone should be such that when the molybdenum source reaches 100°C below the preset temperature, the sulfur source reaches the preset temperature to provide a sulfur-rich environment. Stop heating after 5 minutes of insulation and cool naturally to room temperature. The flow rate of the carrier gas remains unchanged during the cooling process.

[0095] The obtained MoS2 nanosheet material was deposited on a silicon dioxide substrate. The microscopic morphology and crystal domain size of the nanosheet were tested using an optical microscope; the thickness of the nanosheet was tested using an atomic force microscope; the uniformity of the luminescence of the nanosheet and the evidence of the crystal domain size were tested using a fluorescence microscope. The results showed:

[0096] Figure 4 This is a microscope observation result of the two-dimensional transition metal sulfide nanosheet of this example.

[0097] Depend on Figure 4 It can be seen that the synthesized nanosheets have a triangular morphology with neat edges and an average lateral size of about 40 μm.

[0098] Figure 5 1 is the atomic force microscopy result of the two-dimensional transition metal sulfide nanosheet of this example.

[0099] The thickness of the MoS2 nanosheets is 0.76 nm.

[0100] Figure 6 This is a fluorescence microscope image of the two-dimensional transition metal sulfide nanosheet of this embodiment.

[0101] It shows that the obtained MoS2 nanosheets have uniform fluorescence properties.

[0102] Figure 7 is the Raman image of the two-dimensional transition metal sulfide nanosheet of this embodiment.

[0103] This spectral peak corresponds to the Raman characteristic peak of molybdenum disulfide nanosheets, indicating that the obtained material is a pure molybdenum disulfide nanosheet material.

[0104] Example 2

[0105] This embodiment prepares a two-dimensional transition metal sulfide nanosheet, and the specific process is different from that of embodiment 1 in that:

[0106] (1) In step D2, the transition metal source is tungsten trioxide instead of tungsten trioxide;

[0107] (2) In step D3, the temperature of the second heating zone (transition metal source) is 820°C.

[0108] Figure 8 This is a microscope observation result of the two-dimensional transition metal sulfide nanosheet of this example.

[0109] Depend on Figure 8 It can be seen that the synthesized tungsten disulfide nanosheets have a triangular morphology with neat edges and an average lateral size of about 47 μm.

[0110] Fig. 9 This is the atomic force microscopy result of the two-dimensional transition metal sulfide nanosheet of this example.

[0111] The thickness of the tungsten disulfide nanosheet is 0.79nm.

[0112] Fig.10 This is the Raman image of the two-dimensional transition metal sulfide nanosheet of this embodiment.

[0113] This spectrum peak corresponds to the Raman characteristic peak of tungsten disulfide nanosheets, indicating that the obtained material is a pure tungsten disulfide nanosheet material.

[0114] Example 3

[0115] This embodiment prepares a two-dimensional transition metal sulfide nanosheet, and the specific process is different from that of embodiment 1 in that:

[0116] (1) In step D2, the transition metal source is manganese dioxide instead of tungsten trioxide;

[0117] (2) In step D3, the temperature of the second heating zone (transition metal source) is 720°C.

[0118] Fig.11 This is a microscope observation result of the two-dimensional transition metal sulfide nanosheet of this example.

[0119] Depend on Fig.11 It can be seen that the synthesized manganese sulfide nanosheets have a triangular morphology with neat edges and a lateral size of about 20 μm.

[0120] Fig.12 This is the atomic force microscopy result of the two-dimensional transition metal sulfide nanosheet of this example.

[0121] Depend on Fig.12 It can be seen that the surface of the manganese sulfide nanosheet is clean and its thickness is about 10 nm.

[0122] Comparative Example 1

[0123] This comparative example prepares a method for preparing molybdenum disulfide nanosheets, which is different from Example 1 in that:

[0124] (1) does not include step D1;

[0125] (2) In step D2, sulfur powder is directly used as the sulfur source.

[0126] Fig.13 This is an optical microscope image of the molybdenum disulfide nanosheets obtained in this comparative example.

[0127] The results show that the microscopic morphology of the obtained nanosheets is also triangular, and the crystal domain size is about 30μm.

[0128] Comparative Example 2

[0129] This comparative example prepares a method for preparing molybdenum disulfide nanosheets, which is different from Example 1 in that:

[0130] (1) Polyacrylonitrile sulfide is not treated with discharge.

[0131] (2) Using sulfurized polyacrylonitrile that has not been subjected to discharge treatment as the sulfur source.

[0132] Fig.14 This is an optical microscope image of the molybdenum disulfide nanosheets obtained in this comparative example.

[0133] The results show that the microscopic morphology of the obtained nanosheets is concave triangle and the crystal domain size is about 10μm.

[0134] Effect verification

[0135] The optical and crystal quality of the two-dimensional transition metal sulfide nanosheets were characterized by room temperature and low temperature photoluminescence spectroscopy and scanning transmission electron microscopy. The laser wavelength of the photoluminescence spectrum was 532nm.

[0136] Fig.15 This is the room temperature photoluminescence spectrum of the molybdenum disulfide nanosheets obtained in Example 1 of the present invention.

[0137] The results showed that the obtained material had a very sharp photoluminescence peak with a half-peak width of about 47meV, which is the lowest value among all molybdenum disulfide nanosheets reported so far, indicating that the material has excellent optical properties.

[0138] Fig.16 This is the low-temperature (80K) photoluminescence spectrum of the molybdenum disulfide nanosheets obtained in Example 1 of the present invention.

[0139] The results show that the defect peak area of ​​the material accounts for a low proportion of the luminescence spectrum peak area, indicating that the sulfur defect density of the material is very low.

[0140] Fig.17 This is the room temperature photoluminescence spectrum of the tungsten disulfide nanosheets obtained in Example 1 of the present invention.

[0141] The results show that the photoluminescence peak of the obtained tungsten disulfide is also very sharp, with a half-peak width of about 41 meV, indicating that the obtained tungsten disulfide nanosheets have excellent optical properties.

[0142] Fig.18 This is the room temperature photoluminescence spectrum of the molybdenum disulfide nanosheets obtained in Comparative Example 1 of the present invention.

[0143] In Comparative Example 1, sulfur powder was used as the sulfur source, and the photoluminescence test conditions of the obtained molybdenum disulfide nanosheets were the same as those in Example 1. The results showed that the half-peak width of the photoluminescence spectrum of the material in Comparative Example 1 was about 70 meV, and the optical performance was poor.

[0144] Fig.19 This is the low-temperature (80K) photoluminescence spectrum of the molybdenum disulfide nanosheets obtained in Comparative Example 1 of the present invention.

[0145] The results show that the defect peak area of ​​the material accounts for a high proportion of the luminescence spectrum peak area, indicating that the material prepared in Comparative Example 1 contains more defects.

[0146] Fig. 20 This is the room temperature photoluminescence spectrum of the molybdenum disulfide nanosheets obtained in Comparative Example 1 of the present invention.

[0147] In Comparative Example 2, undischarged sulfurized polyacrylonitrile was used as the sulfur source, and the photoluminescence test conditions of the obtained molybdenum disulfide nanosheets were the same as those in Example 1. The results showed that the half-peak width of the photoluminescence spectrum of the material in Comparative Example 1 was about 67 meV, and the optical performance was poor.

[0148] Fig.21 This is a scanning transmission electron microscope image of the molybdenum disulfide nanosheet material obtained in Example 1 of the present invention.

[0149] The results showed a clear six-membered ring structure with a sulfur defect density of ≤10 13 Pieces / cm 2, further indicating that the material has a low sulfur defect density and ultra-high crystal quality.

[0150] In summary, the method provided by the present invention can significantly reduce the sulfur vacancy defect density in the lattice and improve the crystal quality and optical quality of the obtained two-dimensional transition metal sulfide nanosheets by replacing the sulfur source with sulfur powder and sulfurized polyacrylonitrile that has been discharged.

[0151] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A method for preparing a two-dimensional transition metal sulfide nanosheet, characterized in that: The method comprises the steps of carrying out chemical vapor deposition reaction on a substrate using a sulfur source and a transition metal source as preparation raw materials, wherein the sulfur source is sulfurized polyacrylonitrile powder treated by discharge, and the transition metal source is at least one of molybdenum trioxide powder, tungsten trioxide powder or manganese dioxide powder.

2. The preparation method according to claim 1, characterized in that: In the chemical vapor deposition reaction, the heating temperature of the sulfur source is 100-500°C.

3. The preparation method according to claim 1, characterized in that: In the chemical vapor deposition reaction, the heating temperature of the transition metal source is 400-1200°C.

4. The preparation method according to claim 1, characterized in that: The chemical vapor deposition reaction is carried out with the assistance of a carrier gas; preferably, the carrier gas includes at least one of nitrogen and argon.

5. The preparation method according to claim 4, characterized in that: With respect to the flow direction of the carrier gas, the sulfur source is located upstream of the metal source, and the substrate is located above the metal source.

6. The preparation method according to claim 1, characterized in that: The substrate includes silicon dioxide, sapphire or mica.

7. The preparation method according to claim 1, characterized in that: The method for preparing the discharge-treated sulfide polyacrylonitrile powder comprises: assembling sulfide polyacrylonitrile as the positive electrode of a lithium-sulfur battery, and performing a constant current discharge treatment on the battery; preferably, the current is 0.1C; preferably, the discharge time is 10 hours; preferably, the method for preparing the discharge-treated sulfide polyacrylonitrile powder further comprises collecting the discharge-treated sulfide polyacrylonitrile powder, washing it with N-methylpyrrolidone and anhydrous ethanol in sequence, and drying it, and the collected black powder is the discharge-treated sulfide polyacrylonitrile powder.

8. The preparation method according to any one of claims 1 to 7, characterized in that The molar ratio of the transition metal source to the sulfur source is 1:3-150.

9. A two-dimensional transition metal sulfide nanosheet, characterized in that: Prepared by the preparation method described in any one of claims 1 to 8.

10. The two-dimensional transition metal sulfide nanosheet according to claim 9, characterized in that: The point defect density of the two-dimensional transition metal sulfide nanosheet is ≤10 13 Pieces / cm 2 ; Preferably, the thickness of the two-dimensional transition metal sulfide nanosheet is 0.7-10 nm; Preferably, the crystal domain size of the two-dimensional transition metal sulfide nanosheet is 5 to 100 μm.

Citation Information

Patent Citations

  • Method for preparing self-supporting transition-metal disulfide / carbon composite film

    CN105514446A

  • Room temperature sodium-sulfur battery positive electrode material and preparation method and application thereof

    CN110098390A

  • Two-dimensional transition metal sulfide and preparation method and application thereof

    CN114959636A

  • Preparation method of sulfurized polyacrylonitrile positive electrode material for lithium-sulfur battery

    CN116960331A

  • Carbon-coated lithium sulphide

    EP3063811A1